Ctenostomatous Bryozoa from São Paulo, Brazil, with descriptions of twelve new species - Vieira, Leandro M.; Migotto, Alvaro E.; Winston, Judith E. (Zootaxa, 2014)
This paper describes 21 ctenostomatous bryozoans from the state of São Paulo, Brazil, based on specimens observed in vivo. A new family, Jebramellidae n. fam., is erected for a newly described genus and species, Jebramella angusta n. gen. et sp. Eleven other species are described as new: Alcyonidium exiguum n. sp., Alcyonidium pulvinatum n. sp.,                       Alcyonidium torquatum n. sp., Alcyonidium vitreum n. sp., Bowerbankia ernsti n. sp., Bowerbankia evelinae n. sp., Bowerbankia mobilis n. sp., Nolella elizae n. sp., Panolicella brasiliensis n. sp., Sundanella rosea n. sp., Victorella araceae n. sp. Taxonomic and ecological notes are also included for nine previously described species: Aeverrillia setigera (Hincks, 1887), Alcyonidium hauffi Marcus, 1939, Alcyonidium polypylum Marcus, 1941, Anguinella palmata van Beneden, 1845,     Arachnoidella evelinae (Marcus, 1937), Bantariella firmata (Marcus, 1938) n. comb., Nolella sawayai Marcus, 1938, Nolella stipata Gosse, 1855 and Zoobotryon verticillatum (delle Chiaje, 1822).